Harmonic structure hydraulic binder, preparation method thereof and strength decoupling high elastic modulus cement-based composite material prepared from harmonic structure hydraulic binder

By adopting the core-shell harmonic structural design of a continuous three-dimensional network and the bimodal core-shell cluster filling mechanism in cement matrix composites, the problems of high cost, high brittleness and slow hydration rate in the improvement of elastic modulus and strength of existing cement matrix composites are solved, and the production of gelled composites with low carbon, high elastic modulus and moderate strength is achieved.

CN119546826APending Publication Date: 2025-02-28PIAO JIANLIANG TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202280095777.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2022-09-29
Publication Date
2025-02-28

AI Technical Summary

Technical Problem

While improving the elastic modulus and strength, existing cement-based composite materials have problems such as high cost, limited production, high brittleness and slow hydration rates, which are difficult to meet the sustainable development needs of the construction industry.

Method used

The core-shell harmonic structure design of a continuous three-dimensional network is designed, and the blast furnace slag is formed by ultra-fine abrasive granulation to form a hydraulic cement-based adhesive that acts directly. Combining the organic structure guide agent and low water ratio, a bimodal core-shell cluster filling mechanism is formed to achieve the formation of a hydrate gel layer with high bond density.

Benefits of technology

The production of gelled composite materials with low carbon footprint, high elastic modulus and moderate strength has been achieved, which reduces production costs, improves production efficiency, solves the problems of brittleness and hydration rate, and meets the sustainable development needs of the construction industry.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 00000000_0000_ABST
    Figure 00000000_0000_ABST
Patent Text Reader

Abstract

The present invention relates to improved cementitious composite elements, in particular to novel strength-decoupled high elastic modulus cementitious composites (10); to a novel harmonic structure hydraulic binder composition (11) suitable for the production of such cementitious composites; to a method for producing such hydraulic binders and such cementitious composites; relates to the use of specific mechanical-chemical dry milling (90) and organic structure directing agents (80) in hydraulic binders and cement mixtures. The compositions of the present invention comprise an effective amount of bimodal coarse and ultrafine hydraulic particles (21), (27) forming a core-shell self-assembled cluster matrix. The cementitious composite elements according to the invention exhibit significantly improved elastic modulus and durable material properties, particularly for structural deformation and sustainability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention broadly relates to an innovative form of cementitious composite system having a novel core-shell harmonic structure hydraulic binder matrix that provides outstanding strength-decoupled elastic modulus mechanical properties compared to prior art ultra-high performance cementitious composite (UHPC) material approaches. In contrast to the UHPC approach that achieves high elastic modulus by employing extremely low water / cementitious binder-filler ratios and specific reactive aggregates, the strength-decoupled high elastic modulus cementitious composite of the present invention utilizes a core-shell harmonic structure design of a continuous three-dimensional network that constitutes a high bond density epitaxially grown hydraulic cementitious binder gel layer microstructure that is fundamentally different from ordinary cementitious binder gels. This enhanced behavior is fundamentally related to the rare ability to use an organic structure directing agent as a fundamental step in tailoring the synergistic effect of the core-shell harmonic structure hydraulic cementitious binder cluster. It is obvious that the present invention provides an energy-efficient and shear-friction-reducing process for producing ultrafine particles of direct hydraulic cementitious materials using blast furnace slag to replace the low-yield air classification production route of the prior art, thereby achieving the production of cementitious composite materials with low carbon footprint, high elastic modulus and moderate strength. From a materials engineering perspective, the focus of the present invention is to advance a holistic approach to design and manufacture new cementitious composite materials that meet the challenges of sustainable development in the construction industry. Prior art cement-based composite materials technology

[0002] Building materials provide the basic structure of modern civilization; they must be cheap and easily available. Cement-based composites such as concrete are the main building materials facing a wide range of challenges today, such as rapid construction cycles and high performance requirements, many of which are related to the need for sustainable development, reduced raw material consumption, reduced energy used in processing and increased service life. The modulus of elasticity of concrete, as shown in Figures 1a and 1b, is necessary for analyzing the deformation of buildings and civil structures under dynamic loads, especially wind and seismic loads. It is also used to determine the modulus ratio, m. The modulus of elasticity depends on the compressive strength of the concrete, the nature of the coarse aggregate, the proportion of aggregate in the concrete and the addition of mineral admixtures. The maximum practical size of the aggregate specified and the appropriate concrete grading can result in a higher content of coarse aggregate in the concrete mix. As long as the aggregate used has a high modulus of elasticity, such concrete tends to have a higher modulus of elasticity. However, increasing the size of coarse aggregate may result in a reduction in the strength of a high-strength concrete mix because the cement paste fails when bonding with the coarse aggregate. Increasing the paste content and reducing the water-cement ratio will increase the elastic modulus, so ultra-high performance concrete (UHPC) composite technology with very high compressive strength and higher elastic modulus is a well-known technology in the construction industry. For example, in order to increase the elastic modulus by 20%, it may be necessary to increase the compressive strength by 50%. High-strength, high elastic modulus concrete is often used for columns, shear walls of high-rise buildings, long-span bridges, parking lots, and offshore structures that require higher density, lower permeability, and improved resistance to freezing, thawing, and corrosion. In these applications, designers can take full advantage of the increased compressive strength and elastic modulus to reduce the amount of steel, reduce the size of structural members (increasing the usable floor space in high-rise buildings), or build additional floors.

[0003] Referring to Figures 2a and 2b, the typical elastic modulus of concrete related to the compressive strength of concrete is given by various structural design regulations used by designers for stability checks of structural engineering. By using the most commonly used granite aggregate, the elastic modulus of concrete with a compressive strength of 60 MPa at 28 days is around 30 GPa to 32 GPa. Referring to Figures 3a and 3b, the elastic modulus of concrete with different types of aggregates related to the compressive strength of concrete is shown. The elastic modulus of concrete with a compressive strength of 60 MPa using reactive aggregates such as basalt is around 45 GPa to 47 GPa at 28 days. However, reactive aggregates may cause alkaline silica reaction problems in hardened concrete, and design regulations specify special treatment methods to control this problem. Pressure in the concrete industry to reduce construction schedules has resulted in concrete members being subjected to loads long before the conventional 28-day curing period is complete. A good understanding of compressive strength, elastic modulus, splitting tensile strength and Poisson's ratio is required for safe formwork demoulding and early load application. Referring to Figure 3c, typical rates of development of physical properties of concrete at early ages are shown, with the results showing that the elastic modulus develops much faster than tensile or compressive strength, which develop at approximately the same rate. It was observed that the period within the first 12 hours after casting is the period of fastest development of physical properties. In particular, the static elastic modulus is the most important property of concrete. It is an essential parameter necessary for estimating prestress loss and predicting early buckling loads in long columns. In the construction industry, based on the use of Figure 4a The fiber-reinforced ultra-high performance concrete technology shown is generally referred to as UHPC, and its most famous high-performance products are Ductal and Dura. However, Ductal and Dura are mainly used in the precast industry, but for one cubic meter of concrete, in order to achieve an elastic modulus of 45GPa and a compressive strength of 150MPa, the content of Portland cement exceeds 700kg. Figure 4b In the present study, the effect of aggregate type on the variation of elastic modulus values ​​in UHPC composites was again observed, similar to that in normal strength concrete. It is also known that the existing production technology of ultrafine slag is limited to the wind classification method with very low yield. Figure 5a and 5b , a typical two-stage production route using an impact-based vertical roller mill method is proposed for grinding slag with a particle size of no more than 15 microns, and a small portion of ultrafine particles can only be extracted by a multi-cyclone air classifier. In order to replace Portland cement clinker with potentially hydraulically hardened granulated blast furnace slag (GGBS) on a larger scale, processing GGBS to a particle size of less than '5' microns should be the goal of activating GGBS to form a direct-acting hydraulic binder. However, due to economic reasons, the currently used process technology cannot achieve this goal. Therefore, there still exists a clear need in the art for moderately strong high elastic modulus cementitious composites that can be used for structural applications and meet the current performance requirements of design codes, with innovative low carbon content active robust cementitious composite design and manufacturing methods ready for large-scale adoption while eliminating all the above-mentioned limitations known to date, such as high cost, limited production volume, high brittleness due to ultra-high strength, and slow hydration rate. Key issues in the current development of high-performance cement composites

[0004] Deflection is an important serviceability limit state to be met in the design of architectural and civil engineering structures (e.g., high-rise buildings, bridges, etc.) that usually use reinforced concrete. Usually, designers have to use large cross-sectional areas of beams and columns to control structural deformation because the stiffness of the structure is much more critical than the strength of high-rise buildings and bridges. Undoubtedly, increasing the elastic modulus of concrete itself is much more effective in terms of sustainability requirements than increasing the size of structural components. Established design codes and concrete regulations regarding strength-coupled elastic modulus practices have been published and widely used to cater to the higher performance of reinforced concrete (e.g., ultra-high performance fiber reinforced concrete with 150 MPa strength for an elastic modulus of 45 GPa) structures. The development of moderate strength high elastic modulus concrete can save building materials from the perspective of environmental and economic benefits, and can also increase the usable area inside high-rise buildings. Concrete consists of granular materials (i.e., aggregates or fillers) embedded in a hydrated matrix gel of cementitious materials (i.e., cement and / or other binders) that fills the spaces between the aggregate particles and glues them together. The bond strength and structural properties of the microstructure of the cohesive hydrated gel vary with the volume of space to be filled and the hydration mechanism. The high performance cementitious composites of the prior art are limited by adjusting the components inside the concrete or the ratio between them and the incorporation of pozzolanic byproducts or mineral admixtures without enhancing the inherent strength of the cement matrix by increasing the total number of effective chemical bonds per unit area of ​​the matrix material. In contrast to conventional cement matrix processing, the present invention focuses on new processing strategies and techniques to control the microstructure of cement hydrate crystal growth and realize the new concept of "strength decoupled high elastic modulus cementitious composites". Current key issues in the production of direct-acting hydraulic binders from ground granulated blast furnace slag

[0005] Ground granulated blast furnace slag (GGBS) is a glassy granular material consisting essentially of silicates and aluminosilicates of calcium and other oxides. Blast furnace slag has a latent hydraulically active characteristic, i.e., when exposed to water, it develops cement properties very slowly with a very slow hydration process due to the formation of an impermeable aluminosilicate film on the surface. The low reactivity of the slag limits its use in slag silicate cement and any other application in which the reactivity of the slag is important. In existing applications, blast furnace slag does not actively participate in the early hydration reaction; due to the large particle size effect, its hydration is very slow and incomplete. In fact, the GGBS materials that remain most active for hydraulic reactivity in cement-based binder systems typically have a particle size of about '1'-'5' microns and a fineness of about 7000-10,000 cm2 / g. Attrition mills are now widely used to grind solids to a sub-sieve size range of less than about 10 microns. However, the mechanical activation process of blast furnace slag eventually destroys the stability of the impermeable aluminum silicate surface film, which is related to the specific conditions of the mill. In other words, it depends on the grinding mechanism and the grinding dynamics. Therefore, the problem of providing energy-saving attrition mills of the type used for large-scale production of ultrafine blast furnace slag remains unsolved. Improvements in microstructure design of high performance metallic materials

[0006] Interestingly, ultrafine-grained and heterostructured materials have attracted great attention in the materials research community due to their excellent mechanical and functional properties. Figure 6b, the formation of harmonic structures in metals and alloys is a new material design paradigm that allows for enhanced strength-ductility structural properties. By using mechanical milling such as jet milling to obtain a bimodal "harmonic" structure in a metal powder, followed by a spark plasma sintering process, a three-dimensional network of equiaxed ultrafine-grained shells surrounding a coarse-grained core region is formed to produce an innovative structural metal material with a specific microstructure for promoting uniform distribution of strain during plastic deformation and for avoiding localized plastic deformation in the early stages of deformation. The benefits of the "harmonic" structure observed in the applicability of this microstructure design can be extended to a wide range of metallic materials, regardless of the nature of the material, phase or crystal structure. However, this prior art practice does not suggest incorporating this or similar principles for use in any type of cementitious material. The concept of three-dimensional arrangement of harmonically structured hydrate gel microstructures is not suggested by any research community for the simple reason that those skilled in the art believe that such intricate arrangement of cementitious matrix binders involves unnecessary expense and difficulty without any expectation of technical benefit. Therefore, the problem of providing a cementitious composite matrix with an improved ordered network structure remains unsolved. Harmonic microstructural control of high elastic modulus hydraulic binder materials

[0007] The main object of the present invention is to provide new cementitious composite materials with improved performance characteristics, in particular under static and dynamic deformation conditions. One aspect of the present invention represents a further development of building materials having a harmonic structural microstructure as described above, enabling the production of cementitious composite materials having great resistance to deformation under both static and dynamic conditions and also exhibiting strength decoupling properties. The novel cement-based composite material of the present invention is unique in that it exhibits high deformation resistance in all three directions and is able to establish an optimal method for incorporating granulated blast furnace slag into the cement matrix phase to utilize its contribution to elastic modulus and durability. The method of incorporating ultrafine slag into the formation of a three-dimensional cement hydrate gel network is of great significance to the development of the novel strength-decoupled high elastic modulus cement-based composite material of the present invention. It requires innovations in ultrafine grinding of hydraulic binder materials, template-based bimodal cluster processing, and low water ratio of the mixed phase to obtain harmonic structural microstructural control in the matrix gel. All of these features play an important role in the formation of a continuously connected network hydrate gel formed by bimodal core-shell clusters. More details regarding these novel features and advantages will be presented now in the corresponding summary of the invention and later in the detailed description of the invention. Summary of the invention Strength decoupled high elastic modulus cement-based composites

[0008] From a systemic perspective, the present invention can be described as a heterogeneous binary cementitious binder composite system characterized by (a) a unique harmonic structured direct-acting hydraulic cement matrix binder phase, (b) a latent water hardness-gel cement matrix filler phase, (c) a coarse-to-fine aggregate skeleton inclusion phase, and (d) a soft organic dispersant based on a mixture composite ratio rule at a low water / cementitious binder-filler ratio.

[0009] In addition to the above-mentioned system perspective, the present invention further proposes a new bimodal core-shell cluster packing mechanism for “coarse-grained core (CGC)”–“ultrafine-grained shell (UGS)” particles generated by continuously connected network hydrate gels to replace the traditional random cement matrix arrangement.

[0010] Another feature of the present invention is to provide a novel ultrafine dry grinding method for preparing an ultrafine particle size shell hydraulic cement-based material by activating the latent hydraulic hardness of finely ground granulated blast furnace slag to form a direct acting hydraulic cement-based binder. Organic structure-directing agents tune pre-nucleated bimodal core-shell clusters

[0011] It is well known that ultrafine pulverized blast furnace slag with particle size below '10' microns will become negatively charged on the surface of the material. According to the preferred and best embodiment of the present invention, from the perspective of hydrated formed crystals, the proposed processing strategy is to use organic polycationic additives as (a) ultrafine slag bridging-stabilization dispersants, (b) bimodal core-shell subunit topology directing agents and (c) flow promoters in combination with anionic comb polymer dispersants. Morphology-controlled epitaxial growth of hydrate gels

[0012] As described above, the present invention also proposes a constraint-based morphological transformation control to promote the formation of a continuous epitaxial layer of hydrated gel products covering the surface of the coarse-grained core. According to the preferred and best mode embodiments of the present invention, from the perspective of space constraints and processing strategies, it is proposed to use (a) low water / cement-based binder-filler ratio as gel-space packing control, (b) bimodal core-shell as optimized binder packing and (c) higher powder-aggregate ratio in the skeleton inclusion phase. Device that realizes new type of attrition grinding activation

[0013] As mentioned above, the present invention also proposes a special device for mechanical activation treatment of active blast furnace slag. According to the preferred and best mode embodiment of the present invention, from the point of view of wear and processing strategy based on shear friction, it is proposed to use (a) dry horizontal technology to eliminate gravity effects, (b) special flat spiral expansion agitator elements as ultra-fine grinding method based on friction shear and (c) specific organic polymers as pulverized agglomeration inhibitors and surfactants. These and various other features and advantages of the present invention, as well as the features and advantages provided, will become more fully apparent from the following detailed description read in conjunction with the accompanying drawings and the appended claims. BRIEF DESCRIPTION OF THE DRAWINGS

[0014] (Fig. 1a) Prior art showing typical concrete strength-elastic modulus requirements in high-rise building design. (Fig. 1b) The prior art shows a typical concrete strength-elastic modulus linear relationship not exceeding 45 GPa.

[0015] (Fig. 2a and b) Prior art showing typical concrete strength-elastic modulus coupling relationship in codes and regulations.

[0016] (Fig. 3a and b) Prior art showing typical aggregate type-elastic modulus coupling relationships in codes and regulations. (Fig. 3c) Schematic diagram showing the rate of development of early concrete physical properties and the type of binder material.

[0017] ( Figure 4a ) The prior art shows the elastic modulus values ​​of ultra-high performance fiber concrete in commercial products. ( Figure 4b ) The prior art shows the influence of aggregate on the elastic modulus value of ultra-high performance fiber concrete.

[0018] ( Figure 5a and 5b ) The prior art shows a method for ultrafine grinding and granulating blast furnace slag by wind classification.

[0019] ( Figure 6a ) The prior art shows typical cement materials and a randomly arranged cement matrix phase. ( Figure 6b ) Prior art shows harmonic structural metal alloy microstructure designs.

[0020] ( Figure 7a ) schematic diagram shows the range of strength-decoupled high elastic modulus cement-based composite materials mentioned in the present invention. ( Figure 7b ) Schematic diagram showing the range of strength-decoupled high elastic modulus cementitious composites compared to the range based on regulations. ( Figure 7c ) Schematic diagram showing the unique harmonic structure cement matrix phase mentioned in the present invention. ( Figure 7d ) Schematic diagram showing the unique bimodal coarse-grained core-ultrafine-grained shell stacking and topological chemical hydration process mentioned in the present invention.

[0021] ( Figure 8a ) Schematic diagram showing the hydration process of the unique harmonic structure high elastic modulus cement-based adhesive matrix mentioned in the present invention. ( Figure 8b ) Schematic diagram showing the change in the rate of development of the elastic modulus at different water-cement-based binder (direct hydraulic binder) ratios mentioned in the present invention. ( Figure 8c ) Schematic diagram shows the overall processing of the unique harmonic structure high elastic modulus cement-based composite material mentioned in the present invention.

[0022] ( Fig. 9 ) Schematic diagram showing the unique harmonic structure high elastic modulus cement composite material overall rules of the mixture proportioning process mentioned in the present invention.

[0023] ( Fig.10 ) Schematic diagram showing the role of unique organic structure directing agents and organic dispersants with core-shell particles.

[0024] ( Fig.11 ) schematic diagram showing the unique planar spiral expansion agitator element and agitator shaft mentioned in the present invention.

[0025] ( Fig.12a ) Schematic diagram showing the unique grinding experiment using organic reagents mentioned in the present invention. ( Figure 12b ) Schematic diagram showing the unique low energy grinding test results of the volume of the present invention.

[0026] ( Fig.13a ) shows the mixing ratio of the cement-based composite material according to the embodiment of the present invention. ( Fig.13b ) Test results of the mixture ratio of cement-based composite materials proposed in the embodiment of the present invention. ( Fig.13c ) The robustness example shows the mixing ratio of the cement-based composite material proposed by the present invention. ( Fig.13d ) The robustness test results of the cement-based composite mixtures proposed in the embodiments of the present invention. DETAILED DESCRIPTION

[0027] Now turn to the attached figure, first refer to Figure 7a , 7band 7c, the novel strength decoupled high elastic modulus cement-based composite material (10) shown in the figure is a multiphase composite material based on the composite mixing rule constructed according to the preferred and best mode embodiment of the present invention. The preferred multiphase composite material includes (a) a direct-acting hydraulic cement matrix binder phase, (b) a potential water hardness-gel cement matrix filler phase, (c) a coarse-to-fine powder-aggregate skeleton inclusion phase, (c) water and an organic structure-directed functionalizing agent, (d) a soft organic dispersant and optionally (e) an organic metal fiber reinforcement phase. The direct-acting hydraulic cement matrix phase is a unique harmonic structure cement matrix phase with a bimodal core-shell cluster (20), which has a heterogeneous binary hydraulic binder composition composed of a direct-acting hydraulic cement binder material. The novel strength-decoupled high elastic modulus cement-based composite material (10) is characterized by an organized three-dimensional network structure formed by the ultrafine-grained shell (UGS) particles (27) covering the unhydrated coarse-grained core (CGC) particles (21), which is composed of a continuously connected, tightly formed cement-based hydrate gel layer (30) to form a bimodal core-shell cluster. The novel composite material shows a unique microstructure array, which has excellent performance in withstanding deformation. This bimodal core-shell cluster (20) with high bonding density between particles stimulates an interlocking strain distribution effect, and it becomes a key feature of the strength-decoupled high elastic modulus cement-based composite material (10) of the present invention. The common direct acting hydraulic cement-based binder material is ground Portland cement clinker with a particle size of '20' microns or more. Instead of ultrafine Portland cement, ultrafine ground granulated blast furnace slag is another direct acting hydraulic cement material, which is selected based on the consideration of reaction rate and silicate composition. However, the excessively fast dissolution rate of ultrafine Portland cement is not suitable for preparing such a stable bimodal core-shell cluster arrangement, which is another main feature of the present invention. Figure 7d As shown, a heterogeneous binary hydraulic binder with bimodal core-shell clusters (20) arranged in a specific spatial topological structure comprises coarse-grained core particles (21) composed of silicate cement particles with positive surface charge and ultrafine-grained shell particles (27) composed of direct-acting hydraulic binder material of granulated blast furnace slag with negative surface charge. The mediation process (40) controls the nucleation and growth of cementitious hydrate morphology and the development of an ordered 3D network structure of the cementitious hydrate gel layer (30). like Figure 8a , 8bAs shown in Figures 8c and 8c, in the proposed novel hydration transformation method, the bimodal core-shell clusters (20) play an important role in generating favorable bonding properties at the interface of the coarse-grained core particles and promoting the epitaxial growth hydration of the direct-acting hydraulic cement-based binder matrix. The bonding is associated with the formation of an alumino-rich calcium silicate hydrate interlayer, which is produced by the interfacial reaction of the coarse-grained core particles (21) with the epitaxial ultrafine-grained shell particles (27) under a low water-cement binder-filler ratio (41) in a confined spatial morphological environment (32). This confined dissolution-based precipitation significantly promotes the precipitation of epitaxial CSH and CASH gel formation, which is produced by the topochemical reaction between silicate ions and dissociated Si and Al with abundant Ca ions released from calcium hydroxide. With the increase of hydration, the bimodal core-shell clusters (20) overlap each other using the epitaxial hydration phenomenon to form cement hydrate gel layers (31). When epitaxially extending near the surface of the coarse-grained core particles, unreacted calcium hydroxide is also precipitated in the cement hydration gel (31), which is formed in the interface region between the coarse-grained core particles (21) and the ultrafine-grained shell, transforming the reaction products formed in the cement hydrate gel layer (30) with an ordered 3D network structure. However, the deposited calcium hydroxide is completely masked within the hydration reaction product layer. Finally, the densely connected cement-based hydrate gel (31) composed of an edge structure with a thickness of about '4' to '10' microns plays a cross-linking and coupling role, playing the role of connecting and wrapping the matrix of the coarse-grained core particles (21). This direct morphological transformation hydration gel growth process (40) occurring on the surface of the coarse-grained core particles (21) forms a typical geometric mesh network structure of the lath-like cement hydration gel (31) associated with the collection of mixed CASH and CSH phases of the ultrafine-grained shell particle (27) structure, thereby revealing the elastic modulus decoupling characteristic structure of the present invention. Reference Figure 8b , low water-cement hydraulic binder ratios (41) effectively shift the elastic modulus development rate from the 6 to 12 hour critical period of early hydration to the 0 to 6 hour critical period, consistent with the requirement for a vigorous direct hydration reaction of ultrafine-grained shell particles (27).

[0028] like Fig. 9 As shown, the new strength-decoupled high elastic modulus cement-based composite material (10) prepared by the grinding and solidification reaction process (60) according to the present invention can be produced with a much lower silicate cement content, which means that carbon dioxide emissions will be significantly reduced, and further enhancement of the elastic modulus can be achieved by adding 5% to 10% ultrafine zeolite powder (61) as a catalyst.

[0029] See Fig.10, organic structure-directing agents (80) are polycationic compounds with quaternary ammonium groups that can be used as bridging agents to strategically coat negatively charged ultrafine ground granulated blast furnace slag hydraulic binder particles. This bridging mechanism drives the formation of core-shell bimodal cluster subunits, thereby making a continuously connected network hydrated gel with the following activities: (a) confining the topochemical reactions within the shell; (b) preparing dense and high-modulus and long-range ordered CSH / CASH crystalline hydrates; and (c) stacking the bimodal cluster subunits together to form a fully densified macrostructure during the pre-mobile self-assembly process. In principle, any material microstructure with a network architecture and improved bonding density for strain resistance will increase its bending resistance and improve its elastic modulus mechanical properties. Thus, by providing fine bimodal core-shell cluster subunits (20) replicated in a substantially uniform and three-dimensional packing arrangement (32) templated by an organic structure directing agent (80), a dramatic breakthrough in the elastic modulus of cement hydrate gel microstructures (31) can be achieved. The most attractive thing about this huge breakthrough deformation resistance of the present invention is that this change in elastic modulus capacity can be achieved by the reactive aggregate component in the new harmonic structure cement matrix without changing the coarse and fine aggregate skeleton containing phase. In other words, the present invention provides a significant strain distribution counteraction between the cement matrix binder phase and the aggregate phase.

[0030] According to the literature, patent survey and available information, there is currently no efficient large-scale production process for producing active ultrafine blast furnace slag by dry mechanical activation, meaning a grinding particle size of less than '10' microns, while inducing surface changes in the solid phase by a shear-friction process. It is not possible to fully hydrate blast furnace slag without adding any chemicals by any method known to date. See for details Fig.11 , the horizontal dry mixer (90) is an ultrafine blast furnace slag stirring mill based on shear friction, which is described as: (a) a flat spirally extended agitator element (91) is arranged laterally on a horizontal rotating shaft (93) at predetermined intervals; (b) the radially outermost end of the agitator element is spaced apart from the inner surface of a grinding container (92), and (c) the outer end of the agitator element is positioned on a spiral line in the grinding container (92). This improved ultrafine dry grinding equipment can be described as a medium kinetic energy horizontal rotary ball mill. The main advantage of dry grinding in a stirred media mill is that the treated material remains dry while grinding in the mill and no moisture needs to be removed after grinding. It thus significantly reduces production costs by eliminating energy-intensive drying equipment. Due to the fact that ultrafine particles show strong reagglomeration behavior when the particle size is less than '5' microns, organic alkanolamine-type surfactant abrasive materials (94) are essential for a successful and scalable mechanical activation process. Reference Fig.12a and 12b , indicating that "DEIPA" N,N-bis(2-hydroxyethyl)-2-propanolamine as an organic surfactant abrasive substance (94) unexpectedly improves the grinding performance of ultrafine blast furnace slag abrasive additives compared with ethylene glycol. It was observed that grinding with DEIPA mainly showed high grinding efficiency and low energy consumption per unit amount of abrasive to produce uniform fineness (Bryan).

[0031] The present invention will be further illustrated in the following non-limiting examples. Example 1 The composition of a novel strength-decoupled high elastic modulus cement-based composite material (10) is now described, and its overall composition is as follows Fig.13a As shown, it comprises a bimodal core-shell hydraulic cement binder phase (11) and heterogeneous binary direct-acting hydraulic cement materials: "coarse-grained core particles (21) - Portland cement particles" and "ultra-fine-grained shell particles (27) - ultra-fine ground granulated blast furnace slag particles" as direct-acting hydraulic reaction-based binder matrix phase; latent hydraulic cement filler matrix phase (23); coarse-fine aggregate skeleton inclusion phase (24): fine powder aggregate and coarse aggregate; soft organic dispersant (25) and fresh water (26). In view of industrial applicability, especially suitable for ready-mix concrete plant adoption, the proposed coarse-fine aggregate skeleton inclusion phase should preferably be limited to common types of mineral rocks, such as fine granite crushed stone and coarse granite crushed stone aggregates. like Fig.13a The cementitious material composition shown can adopt a mixture of specific composition, which is based on a material of a bimodal core-shell hydraulic cement binder (11), which includes ordinary Portland cement (OPC) and ultrafine ground granulated blast furnace slag (UFGGBS), latent ground granulated blast furnace slag (GGBS) cement matrix filler phase combined with a soft organic structure directing agent (80), granite powder and aggregate skeleton inclusion phase (24), a soft organic dispersant (25) and a phosphonate-based organic comb polymer and fresh water (26). The following Table-1 shows the components of the cement matrix phase used to prepare the "new strength-decoupled high elastic modulus cement-based composite material (10)" in Example 1, wherein the cement matrix phase contains a hydraulic binder phase of bimodal core-shell clusters (20) having coarse-grained core particles (21) and ultrafine-grained shell particles (27) determined by weight standards. The test results after 28 days of normal maintenance are shown in Fig.13bThe HOKALS test results are shown in the table. It clearly demonstrates the high-quality core-shell continuous network connected hydrate gel layer interface strengthening strategy and achieves the development of strength-decoupled high elastic modulus cement-based composites without adopting ultra-high strength concrete design methods and / or reactive hard aggregate inclusion methods. Example 2 In a further step, Fig.13c and 13d The cementitious material compositions and test results shown in can illustrate the robustness of the proposed harmonic structural cementitious binder matrix approach using variations in powder-aggregate ratios and water-cementitious binder-filler ratios. Besides the change in the particle size of the granulated blast furnace slag, the proposed novel dry grinding method also has a particular impact on the direct topochemical hydration reaction between the starting materials, which leads to the inventive harmonic structured cement binder matrix microstructure.

[0032] By the best mode for implementing the present invention that has been described in detail, those skilled in the art to which the present invention relates will recognize various alternative designs and embodiments for implementing the present invention defined by the appended claims. All functional equivalents known in the art of any of these materials and methods are included in the present invention. Nevertheless, it is understood that other changes and modifications can be thought of and made by those skilled in the art, and it is our intention that all these other changes and modifications will be understood to be within the spirit of the present invention and the appended claims.

Claims

1. A new type of strength decoupled high elastic modulus cement-based composite material, characterized by: It exhibits excellent high elastic modulus mechanical properties of 40GPa to 50GPa and medium strength mechanical properties of 40MPa to 80MPa; The microstructure of the cement matrix phase plays a leading role in the strength development from the aggregate skeleton inclusion phase through the harmonic structure, avoiding strain localization and strength decoupling behavior and promoting uniformity of deformation; composed of a unique harmonically structured cementitious matrix phase formed by the curing of a heterogeneous binary hydraulic cement binder of bimodal core-shell clusters of coarse-grained core particulate material and ultrafine-grained shell particulate material having a specific spatial topological arrangement; After adding water and organic structure-oriented functionalizing agent, the ultrafine shell particle material envelops the coarse core particle material, and the coarse core particle material is transformed into an organized network structure of cement-based hydrate gel in a continuous and tightly connected form based on the closed topological chemical hydration reaction process; based on the composite proportioning rule of the mixture at a low water / cement-based binder-filler ratio, it further includes a potential water hardness-cementitious cement matrix filler phase, a coarse-fine powder-aggregate skeleton inclusion phase, a soft organic dispersant and an optional organic-metal fiber reinforcement phase; A bimodal core-shell cluster distribution of coarse-grained core and ultrafine-grained shell particulate material having a weight proportion of 75%-45% of coarse-grained particles having an average diameter in the range of equal to or greater than '10' microns; preferably, between '10' and '40' microns; more preferably, between '20' and '30' microns, and having a weight proportion of 25%-55% of ultrafine-grained particles having an average diameter in the range of equal to or less than '10' microns; more preferably, between '3' and '10' microns; more preferably, between '5' and '7' microns; The coarse-grained core particle material containing hydraulically reactive calcium silicate and calcium aluminosilicate building blocks is manufactured by a typical Portland cement clinker grinding process; Ultrafine-grained shell particulate material containing hydraulically reactive calcium aluminosilicate building units obtained by mechano-chemical activated grinding of granulated blast furnace slag with a high alumina (AL2O3) content equal to or greater than 10%, and optionally with natural and / or artificial zeolite powder; The mechano-chemical activated shear and friction grinding method of granulated blast furnace slag includes the steps of using a dry agitated ball mill supplemented with an organic dispersant containing an alkanolamine; During the composite mixing process, the surface of the ultrafine-grained shell particle material is functionalized by a cationic organic structure-directing agent containing a quaternary ammonium surfactant to form a shell layer with a core-shell skeleton network topology with the coarse-grained core particle material; The water / hydraulic cement binder-filler ratio is set in the range of 0.28 to 0.35 to limit the spatial volume of hydration growth and subsequent hydrate solidification morphology; The dominant species in the harmonic structured binding phase, ultrahigh and high elastic modulus CSH and / or CASH hydrates, are produced by spontaneous precipitation through spatially confined interactions between ultrafine-grained shell particle layers and coarse-grained core particle edges by the controlled addition of water and soft organic dispersants; The microarchitecture of strength-decoupled high elastic modulus cementitious composites is controlled by subdividing the latent water hardness-gel filler matrix phase and the coarse-fine-framework inclusion phase into fine and coarse fractions.

2. The strength decoupled high elastic modulus cement-based composite material according to claim 1, further characterized in that: A heterogeneous binary hydraulic binder having: The particle size distribution of the coarse-grained core particle material and the ultrafine-grained shell particle material has a number of peaks, i.e. is multimodal, but has at least two peaks, and is preferably substantially bimodal, i.e. at least 80% by volume (preferably 90% by volume) of the particles are associated with two peaks; The relative volume of the particles in the first peak relative to the volume of the particles in the second peak is 2.5:1.0 to 1.0:1.0, more preferably 1.5 to 1.0; Preferably, the coarse-grained core particle material and the ultrafine-grained shell particle material have substantially similar hydraulic reactivities that serve to produce dense bimodal core-shell clusters with order and direct the local chemical hydration process while solidifying and producing an ordered network structure.

3. The strength decoupled high elastic modulus cement-based composite material according to claim 2, further characterized by: The ultrafine size shell particulate material is prepared by dry agitated ball milling of ground granulated blast furnace slag (GGBS) with a polymeric co-dispersant containing at least one "alkanolamine" preferably diethanol isopropanolamine (DEIPA) as a milling activator; Ground granulated blast furnace slag (GGBS) having a high alumina (AL2O3) content in the range of 10% to 20%, preferably 13% to 17%; more preferably 13% to 15%; The particle size distribution of the ultrafine shell particulate material has a single peak at a size of 5' microns, and the volume of particles associated with the single peak is at least greater than 50%; more preferably greater than 60%; even more preferably greater than 70% by volume.

4. The strength decoupled high elastic modulus cement-based composite material according to claim 1, further characterized by: The organic structure directing agent plays a structural directing role on the ultrafine-grained shell particle material, so that it forms a core-shell maximum stacking structure; The organic structure directing agent with high positive charge electrostatic force effectively attracts the negatively charged ultrafine shell particles and directs the structure of the ultrafine shell particles to be more uniform than a random mixture with coarse core particles in high rheological behavior; The organic structure directing agent is a cationic polymer surfactant containing a quaternary ammonium compound such as a triquaternary amine, which is used to direct the formation of a shell layer of a core-shell skeleton network topology structure derived from a coarse-grained core particle material and an ultrafine-grained shell particle material; The quaternary ammonium organic structure directing agent is formed by a composite of polymer A and compound B, wherein polymer A is obtained by free radical copolymerization of monomer "a" and monomer "b", monomer "a" is selected from (meth)acrylic acid or a mixture of any proportion of monovalent metal salts of (meth)acrylic acid, and monomer "b" is selected from diallyl quaternary ammonium salt derivatives or (meth)acrylamide quaternary ammonium salt derivatives; compound B is fatty acid alkanolamide.

5. The strength decoupled high elastic modulus cement-based composite material according to claim 3, further characterized by: Mechano-chemical activation of granulated blast furnace slag is carried out by a grinding process based on shearing and friction; Shear- and friction-based grinding is a dry grinding process performed in a horizontal stirred ball mill; The dry horizontal stirring ball mill has dedicated stirring elements arranged laterally at predetermined intervals on a horizontal rotating shaft driven by a medium-high speed rotor; The special stirring elements are die-cast metal disks with a proprietary shape configuration, wherein the outer edge of each stirring element extends as a flat spiral extending in a direction opposite to the direction in which it is intended to rotate, so that the grinding body rolls on a contact line with a low gradient; The dry grinding process of the ultrafine-sized shell particulate material is carried out by shearing and friction instead of compression, through the random relative pulverizing media ball motion action caused by the flat spiral stirring elements / disks evenly arranged along the rotating stirrer axis; The mechanochemical activation of the granulated blast furnace slag is assisted by an organic surfactant containing at least one alkanolamine, preferably DEIPA'N,N-bis(2-hydroxyethyl)-2-propanolamine.

6. The strength decoupled high elastic modulus cement-based composite material according to claim 2, further characterized by: The coarse-grained core particle material is selected from the group consisting of Portland cement, Portland composite cement and blast furnace slag cement; The ultrafine particle size shell particle material is selected from the group of blast furnace slag cement optionally with zeolite powder added as a catalyst.

7. The strength decoupled high elastic modulus cement-based composite material according to claim 1, further characterized by: The potential water hardness filler matrix phase is selected from the group of silica fume and fly ash to supplement the cementitious material to consume the excess portlandite CA(OH)2 after hydration; The coarse-fine framework comprises a non-reactive stone filler phase selected from the group consisting of granite, limestone and calcined bauxite; The organic polymer dispersant is a tailor-made anionic comb copolymer selected from the group of polycarboxylic and polyphosphonic acid anchoring groups with polyether side chains as flow enhancers for low water-cement binder-filler ratios.

8. The strength-decoupled high elastic modulus cement-based composite material according to claim 1, characterized in that: The manufacturing method thereof comprises the following steps: (i) dry grinding silicate cement clinker and / or blast furnace slag granules into a particle size distribution (d 95 ) ranges from 20 to 70 μm and the specific surface area ranges from 0.3 to 0.8 m 2 / g of coarse-grained core particle material; (ii) grinding the polymer co-dispersant "alkanolamine" of the granulated blast furnace slag coarse-grained material into a particle size (d 95 ) in the range of 2 to 20 μm and a specific surface area of ​​0.9 to 5 m 2 Ultrafine particle size hydraulic binder material in the range of / g; (iii) providing a mixture of heterogeneous binary hydraulic binders having a unique bimodal distribution from a coarse-grained core particulate material and an ultrafine-grained shell particulate material; (iv) adding a latent water hardness-gel matrix filler phase, a coarse-fine aggregate inclusion phase and an optional organic and / or metal fiber reinforcement phase to a heterogeneous binary hydraulic cement binder based on a mixing rule; (v) adding an organic structure directing agent comprising a quaternary ammonium surfactant to the mixture to form self-assembled bimodal core-shell clusters of coarse-grained core particle material and ultrafine-grained shell particle material with controlled and specific topological particle size distribution; (vi) adding water, a flow enhancer containing an anion carrier polyether chain, and / or other additives according to the optimized constrained cured overall bulk density water / cementitious binder-filler ratio requirements; (vii) mixing the predetermined mixture with a mixing mixer, and (viii) Fabrication of strength-decoupled high elastic modulus cement-based composites.

9. The strength-decoupled high-elastic cement-based composite material according to claim 1, characterized in that: Use of structural components and / or elements in forming reinforced cementitious composite parts for in-situ and / or prefabricated components, the reinforced cementitious composite parts having: The low-portland cement content ranges from 200kg to 300kg per cubic meter of cement composite material, more preferably from 250kg to 275kg; A combination of moderate compressive strength in the range of 45MPa-80MPa and a high elastic modulus in the range of 40GPa-50GPa; For high durability and early strength properties, an optimized water / cement binder-filler ratio in the range of 0.28-0.35, more preferably in the range of 0.30-0.33 is used; For high processability properties, optimized bulk density and high performance superplasticizer dispersants with a combination of carboxylate and phosphonate anion binding groups are used.

10. The strength-decoupled high-elastic cement-based composite material according to claim 1, further characterized by: Substantially as hereinbefore described with reference to the accompanying drawings.